Reformasi Hukum Islam Menurut ‘Abd Allah al-Na’im - M. Zaki Mubarak (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
The article discusses the thought of ‘Abd Allah Ahmad al-Na’im, a contemporary Sudanese Muslim scholar. He offers ideas concerning sensitive issues in Islam, especially in interpreting al-Qur’an and its relation to sharia. This sensitiveness results from the fact that certain verses have dichotomous meaning. Certain Muslim scholars allow interpreting such verses, whereas other do not. As a result, there are unveiled meanings in al-Qur’an that prevent the advancement of Islam. In dealing with the challenge of modernity, ijtihad in the light of sharia is no longer sufficient because there are so many problematic legal aspects and principles in, such as constitutional law, criminal law, international law and human rights. Those rulings are based on texts of al-Qur’an and Hadith which have definite and clear meaning. Therefore, new line of interpretation towards understanding of al-Qur’an, especially those concerning Islamic law, is necessary for Islamic law to remain relevant in our time.